Effect of L-carnitine intake on exercise performance among athletes: a scoping review - Mariadas, Matiusdas S/O (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
L-carnitine is one of the most common ergogenic compounds used in sports, and its efficacy is supported by a strong body of evidence that demonstrated improvement in sport performance especially in aerobic activities. Therefore, this review aims to determine the effect of caffeine consumption on sports performance, types and dosage of caffeine consumed and the timing of its consumption among athletes and physically active individuals. Related studies were searched electronically using the following databases: EbascoHost, JSTOR, SpringerLink and Cambridge. The analysis was done in compliance with the criteria of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). From the 11 studies reviewed, all the studies were conducted on humans. The scope of study from those retrieved articles was primarily on the effects of L-carnitine consumption on sports performance. The total number of participants for all the 11 articles are 176 participants. The study design in these reviewed articles include randomised placebo-controlled trial and double-blind cross-over design